Morality, Markets, and the Gospel of Prosperity - Coleman, Simon (Religion and the Morality of the Market, 2017)
If you walk into any airport bookstore in Europe or North America and head for the section selling advice on how to succeed in business, in relationships, or simply in life there is a good chance that you will find books by Joel Osteen. His bestsellers include Become a Better You: 7 Keys to Improving Your Life Every Day (2009) and Making Wise Choices: Your Decisions Determine Your Destiny (2005). But Osteen is not just a successful author of self-help books; he is also a televangelist renowned in charismatic circles around the world for his prosperity message and for being the head pastor of Lakewood Church in Houston, Texas. His father, John, founded Lakewood Church in the late 1950s and in the process shifted theological positions away from southern Baptism toward a more charismatic, Pentecostal orientation. Arguably, though, Joel has made a still more significant transition in his career, and one that is rarely achieved even in the noisy, confident world of contemporary American televangelists and prosperity preachers. For he has reached a stage at which he not only holds the interest of self-confessed believers – and there are quite a few of those, as Osteen's services are beamed out from Houston to some 100 countries each week – but has also visibly penetrated a global, secular market such as that represented by airport bookstores, which must appeal to generic rather than specifically Christian tastes. Osteen now inhabits a similar niche to that which Norman Vincent Peale made his own in the middle of the twentieth century by offering variations on a theme of positive thinking. He was featured as one of ABC News's “Most Fascinating People of 2006,” and he has had the dubious pleasure of being interviewed on CNN by Piers Morgan. Presidential candidate John McCain called him “inspiring.” In sum, his appeal goes far beyond religion. When I see Joel Osteen's books for sale at airports I often think back to the first interview my colleague Katrin Maier and I did with a member of the Redeemed Christian Church of God in London (RCCG).
paid